Mechanism of Abnormal Coagulation Induced by Tigecycline in Cancer Patients - Sun, Li-Hua; Bai, Kun-Hao; Wu, Guo-Yan; Tian, Xiao-Peng; Zou, Zhi-Qing; Wang, Da-Wei; Dai, Yu-Jun; Chen, Si-Liang (Frontiers in Pharmacology, 2022)
Tigecycline is a broad-spectrum active intravenous antibiotic that is active against methicillin-resistant staphylococcus aureus. In Phase 3 and 4 clinical trials, increased all-cause mortality was observed in patients treated with tigecycline compared to patients in the control group. The reason for the increase is unclear. In this study, we found that tigecycline cause abnormal coagulation in tumor patients, especially in patients with hematological malignancies. The main manifestations were decreased fibrinogen and prolonged activated prothrombin time (APTT), thrombin time (TT), and D-dimer. In addition, through functional studies, we found that tigecycline inhibit platelet adhesion and aggregation, and the coagulation function of patients gradually recover after discontinuation. Gene sequencing results suggested that tigecycline significantly regulate the expression of genes related to platelet function pathways and increase the incidence of single nucleotide polymorphisms and the number of alternative splices in the Chinese hamster ovary (CHO) cells treated with tigecycline. An abnormal function and low numbers of platelets are common in patients with hematological malignancies. Our study can explain the mechanism of abnormal coagulation caused by tigecycline. Additionally, doctors who apply tigecycline to cure infections in tumor patients should be warned.